Profile Analysis of COVID-19 Patients in Jambi Province - Titin Agustin Nengsih; Hafifatul Auliya Rahmy; Guspianto Guspianto; Ummi Kalsum; Hendra Dhermawan Sitanggang; Amirah Saeed Alharthi (Universitas Ahmad Dahlan, 2022)
Background: The potential for COVID-19 transmission has increased sharply, so the government must implement various strategies to control the spread, especially in Jambi Province. The number of positive confirmed cases of COVID-19 in Jambi Province until August 26, 2021, was 27,422 people, with a case fatality rate is 2.37%. This condition illustrates that the spread of COVID-19 is increasing every day, so the government has set a lockdown at Level 4. Method: This research aims to analyze the profile of COVID-19 patients in Jambi Province (secondary data analysis) with a cross-sectional study design. Data analysis includes univariate analysis with the mean difference test and Chi-Square test. Result: The results show that the age of COVID-19 patients is significantly different between men and women. Furthermore, based on the Chi-Square test, it shows a significant relationship between age and gender and between region and age with a p-value <0.05. Conclusion: Indeed, the risk of COVID-19 cases increases with age and differs for each gender with a high level of mobility.